Efgartigimod-alfa therapy in acetylcholine receptor antibody myasthenia gravis: Romanian experience - Nicolae Grecu; Oana Antonia Mihalache; Eugenia Irene Davidescu; Rodica Bălașa; Mihaela Simu; Vitalie Văcăraș; Ileana-Maria Vodă; Andreea-Ioana Mușuroi; Andra Mădălina Ene; Diana Mihaela Petrescu; Cristina Elena Mitu; Lorena Furnică; et al. (Frontiers in Neurology, 2026)
Background Efgartigimod alfa, the first neonatal Fc receptor inhibitor approved for the treatment of acetylcholine receptor antibody (AChR)-positive generalized myasthenia gravis (MG), has demonstrated efficacy in randomized controlled trials. However, real-world data, particularly from Eastern Europe, remain limited. Methods This prospective, multicenter study enrolled AChR-positive generalized MG patients treated with efgartigimod across six Romanian university hospitals between March 2024 and September 2025. Outcomes were assessed using the Myasthenia Gravis Activities of Daily Living (MG-ADL) scale, the Quantitative Myasthenia Gravis (QMG) score, and the Myasthenia Gravis Quality of Life 15-item revised scale (MG-QoL15r). Clinically meaningful improvement (CMI), minimal symptom expression (MSE), patient-acceptable symptom state (PASS), subdomain response, and corticosteroid sparing were evaluated. Results Thirty-nine patients completed at least one treatment cycle, receiving a total of 210 cycles. In cycle 1, CMI rates were 89.7% for MG-ADL and 74.4% for QMG, with a median MG-ADL reduction of 4.0 points ( p < 0.001); 69.2% achieved CMI after a single infusion. Composite PASS increased from 25.6% in cycle 1 to 54.5% in cycle 8. Subdomain analysis showed improvements across all domains for both the MG-ADL and the QMG, with the exception of QMG respiratory. Among patients on corticosteroids ( n = 29), median prednisone dose decreased from 20.0 to 10.0 mg/day ( p = 0.004), with 58.6% achieving reduction or discontinuation. Conclusion This first Eastern European real-world efgartigimod-treated cohort confirms rapid and sustained improvement and corticosteroid sparing, consistent with prior evidence.